The Division of San Pablo City a study of decision-making participation among selected school officials and elective officials - Intarakerd, Sukho Me 1939- ([Quezon City s.n.], 1969)
This study determined the decision-making participation of selected school officials and elective officials in certain aspects of school administration in the Division of San Pablo City in an attempt to identify the area in the school administration in which the participation of elective officials is desirable or undesirable. Findings of the study may serve as a basis for school administrators to deduce ways and means of minimizing, if not eliminating, the unfavorable or disadvantageous effects of the participation of elective officials in the financing of school plant projects and recruitment, placement and promotion of school personnel.
Thesis (M.Ed.)--University of the Philippines
Typescript
Keywords: Education and state -- Philippines -- San Pablo City, Laguna